Heme Peroxidases at Unperturbed and Inflamed Mucous Surfaces - Jürgen Arnhold (MDPI AG, 2021)
In our organism, mucous surfaces are important boundaries against the environmental milieu with defined fluxes of metabolites through these surfaces and specific rules for defense reactions. Major mucous surfaces are formed by epithelia of the respiratory system and the digestive tract. The heme peroxidases lactoperoxidase (LPO), myeloperoxidase (MPO), and eosinophil peroxidase (EPO) contribute to immune protection at epithelial surfaces and in secretions. Whereas LPO is secreted from epithelial cells and maintains microbes in surface linings on low level, MPO and EPO are released from recruited neutrophils and eosinophils, respectively, at inflamed mucous surfaces. Activated heme peroxidases are able to oxidize (pseudo)halides to hypohalous acids and hypothiocyanite. These products are involved in the defense against pathogens, but can also contribute to cell and tissue damage under pathological conditions. This review highlights the beneficial and harmful functions of LPO, MPO, and EPO at unperturbed and inflamed mucous surfaces. Among the disorders, special attention is directed to cystic fibrosis and allergic reactions.